Incidence of major bleeding among oral anticoagulants / Ziran Nadiah Ghazali - Ghazali, Ziran Nadiah (2017)
Oral anticoagulant is widely used in Malaysia to prevent thromboembolic events. Commonly used oral anticoagulants in Hospital Putrajaya are Warfarin, Rivaroxaban and Dabigatran. In patient with atrial fibrillation, the risk of stroke increases to 5-fold in patients and use of anticoagulant therapy reduces the risk of stroke and all-cause mortality. Although proven to be effective, these oral anticoagulants can cause major bleeding. This study was carried out retrospectively in adult patients from INR Clinic with oral anticoagulant. The assessment parameter was incidence of major bleeding event. Among 113 enrolled patients, 19 had a first major bleeding event. It was found that age (OR 1.06; 95% CI 1.02, 1.11) and overwarfarinisation event (OR 1.91; 95% CI 1.26, 2.89) is significant to increase patient’s risk to major bleeding. Comorbid of hypertension (OR 2.66; 95% CI 0.82, 8.63), congestive heart failure (OR 2.44; 95% CI 0.74, 8.00, renal impairment specifically stage 4 (OR 9.00; 95% CI 0.72, 113.02) and stage 5 (OR 6.00; 95% CI 0.42, 85.25), concomitant antiplatelet therapy (OR 0.43; 95% CI 0.13, 1.40), types of oral anticoagulant (novel anticoagulant vs warfarin) (OR 3.42; 95% CI 0.42, 27.58) and TTR (OR 0.96; 95% CI 0.93, 1.00) and other factors studied are not significant in this study. High risk patient should be identified based on the factors exist in them and monitored frequently to minimize the adverse effect of anticoagulant. Patient with first event of major bleeding and especially elderly should be monitored more stringently as they may develop subsequent fatal bleed. Keywords: oral anticoagulant, warfarin, dabigatran, rivaroxaban, major bleeding, bleeding